(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
17 karstic caves of Armenia and 8 caves of Nagorno Karabach are investigated. Brief representation of design of caves, history of their formation and also their biodiversity, in particular structure of their flora and fauna is given.